2021
DOI: 10.1111/aogs.14158
|View full text |Cite
|
Sign up to set email alerts
|

Expectant management for early pregnancy miscarriage after radical trachelectomy: A single hospital‐based study

Abstract: Introduction Women who have undergone radical trachelectomy as a fertility‐sparing treatment for early‐stage cervical cancer may be at higher risk for retained tissues after early‐term miscarriage due to cervical cerclage or cervical necrosis. Dilatation and curettage or aspiration may present additional risks in these women. The aim of this study was to assess the efficacy of expectant management for early pregnancy miscarriage after radical trachelectomy. Material and methods Keio University Hospital records… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…2683 studies were excluded because there were duplicate studies in the databases. After a complete evaluation, 11 articles [ 1 3 , 17 , 18 , 25 30 ] were included in this systematic review, as shown in Figure 1 , comprising 2889 patients undergoing first-trimester miscarriage with 1709 undergoing expectant care for miscarriage in the first trimester. Seven studies [ 1 3 , 17 , 18 , 25 , 29 ] were considered for the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…2683 studies were excluded because there were duplicate studies in the databases. After a complete evaluation, 11 articles [ 1 3 , 17 , 18 , 25 30 ] were included in this systematic review, as shown in Figure 1 , comprising 2889 patients undergoing first-trimester miscarriage with 1709 undergoing expectant care for miscarriage in the first trimester. Seven studies [ 1 3 , 17 , 18 , 25 , 29 ] were considered for the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports have described that expectant management could be useful and appropriate. [19][20][21] Since there is a fear of cervical laceration or intrauterine infection due to aspiration or D&C, expectant management was recommended in our TA B L E 1 Oncologic characteristics in women after radical trachelectomy.…”
Section: Discussionmentioning
confidence: 99%